2019
DOI: 10.1186/s12909-019-1739-z
|View full text |Cite
|
Sign up to set email alerts
|

The journey of thesis supervisors from novice to expert: a grounded theory study

Abstract: Background Supervision is a well-defined interpersonal relationship between the thesis supervisors and their students. The purpose of this study was to identify the patterns which can explain the process of expertise attainment by thesis supervisors. We aimed at developing a conceptual framework/model to explain this development based on the experience of both students and supervisors. Methods We have conducted a qualitative grounded theory study in 20 universities of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…The result of this study was consistent with that of the present study (35)(36)(37)). The results of the study conducted by Steenaart (2019) also showed that the use of new educational methods can increase the knowledge and attitude of nurses in the area of organ donation, which was consistent with the results of this study (38)(39)(40)(41)(42). The results of the studies conducted by Srinivasula et al (2018) and Sugumar et al (2017) and Marqués-Lespier JM (2013) also showed that educational interventions play an important role in increasing the knowledge and attitude of staffs of different medical departments in brain death and organ donation processes and it is necessary to implement educational programs continuously to increase knowledge and improve the performance of the staffs (43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 88%
“…The result of this study was consistent with that of the present study (35)(36)(37)). The results of the study conducted by Steenaart (2019) also showed that the use of new educational methods can increase the knowledge and attitude of nurses in the area of organ donation, which was consistent with the results of this study (38)(39)(40)(41)(42). The results of the studies conducted by Srinivasula et al (2018) and Sugumar et al (2017) and Marqués-Lespier JM (2013) also showed that educational interventions play an important role in increasing the knowledge and attitude of staffs of different medical departments in brain death and organ donation processes and it is necessary to implement educational programs continuously to increase knowledge and improve the performance of the staffs (43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 88%
“…Learning, which is distinct from development, may lead to development and ZPD is the abstraction that describes the mechanism and potential effect of learning on development (Tello, 2012). Bazrafkan, Yousefy, Amini, and Yamani (2019) affirm that supervision may be a well-defined interpersonal relationship between the thesis supervisors and their students. Substantively, Agricola, Prins, van der Schaaf and, van Tartwijk, (2021) research supervision is a complex and subtle form of teaching.…”
Section: Vygotsky's Zone Of Proximal Development (Zpd) and Research Supervisionmentioning
confidence: 83%
“…Ahmadpour et al also examined the correlation of ROP with CRIB score. Of the 256 studied neonates, 180 (70%) had retinopathy in some degrees, of which 56 (31.11%) required treatment, although the relationship between CRIB score and severity of retinopathy was insignificant (P = 0.152); hence, the CRIB cannot predict the severity, progression, or remission of retinopathy (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%